2021
DOI: 10.3390/ijms22094951
|View full text |Cite
|
Sign up to set email alerts
|

IgM and IgG Immunoreactivity of SARS-CoV-2 Recombinant M Protein

Abstract: Diagnostic evaluation of specific antibodies against the SARS-CoV-2 virus is mainly based on spike (S) and nucleocapsid (N) proteins. Despite the critical functions in virus infection and contribution to the pattern of immunodominance in COVID-19, exploitation of the most abundant membrane (M) protein in the SARS-CoV-2 serology tests is minimal. This study investigated the recombinant M protein’s immunoreactivity with the sera from COVID-19 convalescents. In silico designed protein was created from the outer N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…In this study, in addition to confirming that anti-RBD antibodies are long-lasting and antinucleocapsid IgG declines rapidly [3][4][5][6][7] , we show for the first time that anti-membrane IgG is present in the vast majority of COVID-19 convalescent patients and persists for at least a year. Our findings are consistent with findings for IgG against a recombinant membrane antigen (polypeptide of aa 1-19 and 101-222) in the early convalescent period 12 . In contrast, a separate study found that only ~20% of non-hospitalized COVID-19 convalescent subjects had IgG against a similar membrane peptide (aa 1-20) to ours (aa 8-23) in the early convalescent period 13 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, in addition to confirming that anti-RBD antibodies are long-lasting and antinucleocapsid IgG declines rapidly [3][4][5][6][7] , we show for the first time that anti-membrane IgG is present in the vast majority of COVID-19 convalescent patients and persists for at least a year. Our findings are consistent with findings for IgG against a recombinant membrane antigen (polypeptide of aa 1-19 and 101-222) in the early convalescent period 12 . In contrast, a separate study found that only ~20% of non-hospitalized COVID-19 convalescent subjects had IgG against a similar membrane peptide (aa 1-20) to ours (aa 8-23) in the early convalescent period 13 .…”
Section: Resultssupporting
confidence: 92%
“…However, serological testing of anti-membrane protein antibodies is in its infancy. Antibodies against membrane antigens are present days to months after SARS-CoV-2 infection [11][12][13] , but it is unknown how long they persist. Thus, there are currently no widely available serologic tests that uniquely and accurately detect past COVID-19 infection, limiting research and public health efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The global statistical analysis does not take protein structures into account that may make certain epitopes inaccessible. When mapping the responses across the M protein topology [ 22 ], we found that its transmembrane regions are hardly targeted by antibodies, whereas the two extraparticular regions were frequently bound (Figure S2). In fact, the extraparticular N-terminus of M constituted one of the most specific epitopes in the study that was addressed in 88% of positive samples.…”
Section: Resultsmentioning
confidence: 99%
“…So far, only spike and nucleocapsid proteins have been produced in BEV for the diagnosis of COVID-19. The membrane protein of SARS-CoV-2 has been produced in other expression systems such as the E. coli expression system [ 38 ]. Hence, the potential of the M protein to be produced in BEV for diagnostic purposes remains to be explored further, especially with the emerging of new variants that reduce the sensitivity of the current diagnosis of COVID-19 disease [ 39 ].…”
Section: Application Of Baculovirus Expression Vector System (Bev) Fo...mentioning
confidence: 99%